The comparison of thermal tissue injuries caused by ultrasonic scalpel and electrocautery use in rabbit tongue tissue - Guclu Kaan Beriat; Sefik Halit Akmansu; Hande Ezerarslan; Cem Dogan; Unsal Han; Mehmet Saglam; Oytun Okan Senel; Sinan Kocaturk (Biomolecules & Biomedicine, 2012)
The aim of this study compares to the increase in tissue temperature and the thermal histological effects of ultrasonic scalpel, bipolar and unipolar electrosurgery incisions in the tongue tissue of rabbits. This study evaluates the histopathological changes related to thermal change and the maximum temperature values in the peripheral tissue brought about by the incisions carried out by the three methods in a comparative way. To assess thermal tissue damage induced by the three instruments, maximum tissue temperatures were measured during the surgical procedure and tongue tissue samples were examined histopathologically following the surgery. The mean maximum temperature values of the groups were 93.93±2.76 C° for the unipolar electrocautery group, whereas 85.07±5.95 C° for the bipolar electrocautery group, and 108.23±7.64 C° for the ultrasonic scalpel group.